Shapes of distal tibiofibular syndesmosis are associated with risk of recurrent lateral ankle sprains - Qingjun Liu (Nature Portfolio, 2017)
Abstract Distal tibiofibular syndesmosis (DTS) has wide anatomic variability in depth of incisura fibularis and shape of tibial tubercles. We designed a 3-year prospective cohort study of 300 young physical training soldiers in an Army Physical Fitness School. Ankle computed tomography (CT) scans showed that 56% of the incisura fibularis were a “C” shape, 25% were a “1” shape, and 19% were a “Г” shape. Furthermore, we invited a randomly selected subcohort of 6 participants in each shape of DTS to undergo a three-dimensional (3D) laser scanning. The “1” shape group showed widest displacement range of the DTS in the y-axis, along with the range of motion (ROM) on the position more than 20° of the ankle dorsiflexion, inversion and eversion. During the 3-year study period, 23 participants experienced recurrent lateral ankle sprains. 7 cases of the incisura fibularis were “C” shape, 13 cases were “1” shape, and 3 cases were “Г” shape. The “1” shape showed highest risk among the three shapes in incident recurrent lateral ankle sprains. We propose that it is possible to classify shapes of DTS according to the shapes of incisura fibularis, and people with “1” shape may have more risk of recurrent lateral ankle sprains.